PENGEMBANGAN POTENSI NAGARI MALAI V SUKU TIMUR KABUPATEN PADANG PARIMAN - Helmizar Helmizar; Tegar Ryadi; Wulan Febriza (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Nagari Malai V Suku Timur is located in Batang Gasan District, Padang Pariaman Regency, West Sumatra Province, Indonesia. This Nagari is a new Nagari, which resulted from the division of Nagari Malai V Suku in 2017. Nagari Malai V Suku Timur consists of six jorong with a total population of 3285 people with no more than 1000 people in each jorong. Most of the population is still classified as productive, ranging in age from 26 to 55 years. Geographically, Nagari Malai V, the Eastern Tribe, is surrounded by hills, slopes, valleys, and several extensive plains. Such landscape conditions make the majority of the population make a living as farmers. Kenagarian Malai V The Eastern ethnic group faces many problems. Lack of community knowledge resulted in the village's resources not being utilized properly. This activity aims to assist the development of the village by Andalas University students. The method of activities carried out is in synergy to develop the village's potential together with the government and the community by running several programs, including; Community Health Empowerment, Malai Learning House, Malai Indah Park, building a gate and street lamps, happy week, and Malai people's week. In implementing the program, the methods used are lectures, discussions, and practices by conducting a series of counseling and training activities related to the problems found. From the activities that have been carried out, it can be seen that the success is in the form of high enthusiasm and active participation from all levels of society. It is hoped that this activity can benefit the community and overcome existing problems so that Nagari Malai V Suku Timur will be better.